Isolation and Characterization of Lactic Acid Bacteria from Rice Washing Water Waste - Abidin, Zainal; Mudi, Rusmini, La; Hidayat, Nur; Dwi Mentari, Silvi; Daryono, Daryono; Prima, Dody (Publisher Cv. Inara, 2024)
Rice washing water is still considered as household waste because its benefits for plants are not widely known. Rice washing water is obtained from water that is washed many times before cooking which is rich in carbohydrate content in the form of starch and glucose and vitamins. Lactic acid bacteria (LAB) require sugar or carbohydrates from rice washing water which is used as food to support metabolic activity and microbial cell proliferation. LAB is also included in a large group of microorganisms that physiologically produce lactic acid as the main metabolic product. LAB are classified as good bacteria so they are widely used as food processing products, especially those related to human digestion. The use of lactic acid bacteria in the agricultural sector is still very minimal, especially as a biodecomposer, even though LAB has the ability to produce cellulase enzymes which are very important in the breakdown of lignin in organic matter. This study aims to determine the presence of lactic acid bacteria in rice washing water fermentation. Isolation of lactic acid bacteria using pour plate method with MRSA (de Man Rogosa Sharpe Agar) media. Lactic acid bacteria isolates obtained were then characterized morphologically, physically, and biochemically. The results of isolation and characterization obtained four isolates with the codes AL-01, AL-02, AL-03, and AL-04. Four LAB isolates showed gram-positive, catalase-positive, non-motile, non-H2S, and IAA-positive results.